Improving Students’ Speaking Skills Using Tiktok Videos with Procedure Text for the Tenth Grade of MA Al-Amin Tabanan - Ni Putu Era Budiasih (Jurnal Pustaka Cendekia Pendidikan, 2026)
The study aimed to improve students’ speaking skills in delivering procedure texts by using TikTok videos. This research was conducted based on the problems students experienced in speaking, including a lack of confidence and limited vocabulary, which affected their ability to express ideas orally. Therefore, an engaging learning medium was needed to encourage students to practice speaking more actively. The study implemented Classroom Action Research (CAR) conducted in two cycles. The subjects were 14 tenth-grade students of MA Al-Amin Tabanan. The data were collected through speaking tests and observation. The quantitative data were analyzed using mean scores and percentages, while the qualitative data were analyzed descriptively. The results showed that students’ speaking skills improved significantly in each cycle. The mean score increased from 61.1 in the pre-test to 74.3 in Cycle I, and further improved in Cycle II. The percentage of students who achieved the passing grade (KKM) also increased from 21.4% in the pre-test to 57.1% in Cycle I, and showed further improvement in Cycle II. These findings indicate that the use of TikTok videos effectively enhances students’ speaking skills and creates a more engaging learning process.